Larval abundance patterns of Carcinus-Maenas (Decapoda, Brachyura) in Canal de Mira (Ria de Aveiro, Portugal) - Queiroga, Henrique (2013)
Larval stages of Carcinus maenas (L.) were intensively sampled in the Canal de Mira (Ria de Aveiro, Portugal) during 2 lunar months: February 12 to March 11 and May 9 to June 7, 1990. Each sampling period included fifteen 25 h fixed-station sampling cycles beginning at intervals of 4 tide cycles. Within each 25 h sampling cycle, plankton samples were collected hourly at several depths using a pump. Analysis of the data from these sampling periods indicated tidal and diel cycles of abundance of first stage C. maenas larvae. A semilunar component was also identified. These patterns were expressed as peaks of abundance during ebb tides, with highest peaks during nocturnal neap ebb tides around the first and last quarters of the moon. Peaks of nocturnal abundance could occur at any time during the night but consistently followed high water. In contrast, megalopae were present in the samples primarily during nocturnal flood tides. Intermediate zoeal stages of C. maenas were not collected. As indicated by an analysis of variance, the main effects of phases of the tide and day on the abundance of first zoeae and megalopae were significant (p < 0.05). These results provide evidence that a component with semilunar periodicity is associated with the release of C. maenas larvae. That the release activity occurs well after sunset is also an additional interesting feature of these observations, inasmuch as larval release in decapods is usually concentrated within the first few hours after dusk. These observations support earlier observations that it is the time during the day-night cycle of high tide, as opposed to tidal amplitude, which is the important factor promoting synchrony with the lunar cycle.